2018
DOI: 10.1038/s41433-018-0178-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term surgical outcomes of multiple parfoveolar curvilinear internal limiting membrane peeling for myopic foveoschisis

Abstract: Fovea-sparing ILM peeling achieves a higher rate of macular schisis resolution over total peeling. A preoperative outer lamellar macular hole can be a risk factor for the development of a macular hole.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(46 citation statements)
references
References 20 publications
4
42
0
Order By: Relevance
“…In addition, postoperative VA was superior in eyes with fovea-sparing ILM peeling. Similar results have been reported in two other studies (24,25), however, a recent study has argued that there was no difference in the postoperative VA between fovea-sparing and complete ILM peeling groups and that the rate of postoperative MH development was not significant (2/20 vs. 0/13; p = 0.508) (26). The potential benefit of fovea-sparing ILM peeling compared to complete ILM peeling has not been established yet and this needs to be addressed in the future.…”
Section: Myopic Choroidal Neovascularization (Cnv)supporting
confidence: 93%
“…In addition, postoperative VA was superior in eyes with fovea-sparing ILM peeling. Similar results have been reported in two other studies (24,25), however, a recent study has argued that there was no difference in the postoperative VA between fovea-sparing and complete ILM peeling groups and that the rate of postoperative MH development was not significant (2/20 vs. 0/13; p = 0.508) (26). The potential benefit of fovea-sparing ILM peeling compared to complete ILM peeling has not been established yet and this needs to be addressed in the future.…”
Section: Myopic Choroidal Neovascularization (Cnv)supporting
confidence: 93%
“…Although these techniques have showed a better success rate and visual outcome when compared to the classic ILM peeling, no consensus regarding the ILM area to be preserve was developed. A range from 300 to 1000 μ m diameter was reported in different studies [77]. Anatomical results showed the primary success rate limited to 50–73.3% with vitrectomy, ILM peeling, and gas tamponade in high myopic eyes [80].…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Due to thin central foveal tissue, an iatrogenic full-thickness MH could develop during ILM removal. The risk of this complication ranges from 16.7 to 20.8% [ 76 ] and significantly increases in case of outer lamellar macular hole [ 77 ]. To reduce the risk of this complication and to preserve the epifoveal ILM, foveal-sparing ILM peeling procedures were introduced [ 76 79 ].…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…Such adverse events may be even more common in pathological myopia, characterized by long axial length and diffuse chorioretinal atrophy. To prevent postoperative macular hole formation and possible damage to the fovea, a fovea-sparing ILMP technique has been advocated [8,19,20], but some studies have shown that there is no difference in postoperative visual acuity between fovea-sparing ILMP and complete ILMP [9,10].…”
Section: Discussionmentioning
confidence: 99%
“…Many subsequent studies have demonstrated that vitrectomy with internal limiting membrane peeling (ILMP) can be effective in producing both anatomical and functional improvement in MF [3][4][5][6][7]. In order to reduce postoperative macular hole (MH) formation and foveal damage, a partial ILMP technique with foveal sparing was proposed [8], but there is little evidence that this technique has better outcomes than complete ILMP [9,10] Furthermore, more recent studies have shown similar anatomical and functional improvements can be achieved without any form of IMLP [4,11], casting doubt on the benefits of ILMP.…”
Section: Introductionmentioning
confidence: 99%